The melted coins - Dixon, Franklin W. (New York Grosset & Dunlap, 1970)
Suspecting that their friend has been swindled, the Hardy brothers investigate and find themselves on the trail of a much larger criminal operation.
Keywords: Detective and mystery stories -- Juvenile fiction; Mystery fiction